2013
DOI: 10.1098/rspb.2013.1812
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the distribution of breeding and dispersal syndromes in conifers

Abstract: The evolution of plants exhibiting different sexes, or dioecy, is correlated with a number of ecological and life-history traits such as woody growth form and animal-dispersed seeds, but the underlying causes of these associations are unclear. Previous work in seed plants has suggested that the evolution of fleshy cones or seeds may favour dioecy. In this study, we use a well-sampled molecular phylogeny of conifers to show that although dioecy and fleshiness strongly co-occur at the species level, this relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…Ephedra species (mean 5 mya, HPD: 8.1–1.9 mya). Although shifts between dry and fleshy dispersal syndromes in other gymnosperms are less frequent or occurred only a few times in early diverging clades (Leslie et al ), in NW Ephedra most transitions were observed and they appear in either clades that diverged early on or derived clades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ephedra species (mean 5 mya, HPD: 8.1–1.9 mya). Although shifts between dry and fleshy dispersal syndromes in other gymnosperms are less frequent or occurred only a few times in early diverging clades (Leslie et al ), in NW Ephedra most transitions were observed and they appear in either clades that diverged early on or derived clades.…”
Section: Discussionmentioning
confidence: 99%
“…Research on dispersal syndromes in higher plants has mainly focused on differences in the traits that are important for disseminating the seeds (Jordano et al , Masaki et al ) or on understanding the association of different dispersal syndromes with biodiversity and ecological patterns at different scales (Tiffney , Jordano , Griz et al , Beaudrot et al ). However, the ecological consequences of different dispersal syndromes have been rarely studied (but see Leslie et al or Verdú and Pausas ).…”
mentioning
confidence: 99%
“…At the interspecific level, this prediction is relatively well supported by several comparative analyses, mostly in plants (see, e.g. Leslie et al ., ; and references therein; also Eppley & Jesson, for a study using plants, animals and fungi). However, in hermaphrodites, the allocation to the male or female functions can be highly variable between individuals depending, for example on age, mating opportunities and environmental context (Baeza, ; Vizoso & Schärer, ).…”
Section: Introductionmentioning
confidence: 99%
“…A third is a combination of sex inconstancy and long-distance dispersal, allowing establishment in a new location (Baker 1955;Lloyd 1975b;Case et al 2008). Empirical evidence for loss of dioecy varies in strength and approach, ranging from observations of particular forms of sex inconstancy (Lloyd 1975a) to direct genetic studies (Wolf et al 2001;Obbard et al 2006) to phylogenetic reconstructions (Case et al 2008;Volz and Renner 2008;Schaefer and Renner 2010;Leslie et al 2013;Villarreal and Renner 2013;McDaniel et al 2013;Njuguna et al 2013). Empirical evidence for loss of dioecy varies in strength and approach, ranging from observations of particular forms of sex inconstancy (Lloyd 1975a) to direct genetic studies (Wolf et al 2001;Obbard et al 2006) to phylogenetic reconstructions (Case et al 2008;Volz and Renner 2008;Schaefer and Renner 2010;Leslie et al 2013;Villarreal and Renner 2013;McDaniel et al 2013;Njuguna et al 2013).…”
mentioning
confidence: 99%